Genetic and Phenotypic Divergence in a Dung Beetle 50 Years After Its Introduction to Australia - Boikhutso Lerato Rapalai; Leigh W. Simmons; Theodore A. Evans; W. Jason Kennington (Ecology and Evolution)
ABSTRACT Species translocations are increasingly being used in conservation and for biological control. The success of a translocation can be strongly influenced by the evolutionary processes occurring during the early phase of the introduction and the subsequent spread to new regions. In this study, morphological variation and population genetic structure were assessed in the African dung beetle Digitonthophagus gazella, a species that was intentionally introduced to Australia for biological control in 1968 and subsequently spread widely across the northern part of the continent. A dataset based on 1594 neutral single nucleotide polymorphism (SNP) loci that were genotyped in 187 individuals from 12 sites revealed significant genetic divergences between sites (global FST = 0.118) and provides evidence of restricted gene flow among established populations at small to moderate spatial scales (74–500 km). Geometric morphometric analyses revealed significant divergence among populations in the shape of the foretibia, a trait ecologically important for tunnelling in soil and dung. Moreover, phenotypic divergence in this trait for both sexes was significantly higher than genetic differentiation at selectively neutral loci (PST > FST), suggesting that directional selection is contributing to the phenotypic divergences among populations. Our study shows how population structure can establish quickly in an introduced species and highlights the importance of considering local adaptation when performing translocations on established populations.